Technogenic effects on scots pine generative organs: a cross-country study - Assylbekova, Gulmira; Zhumabekova, Bibigul; Klimenko, Mikhail; Shujaul, Mulk Khan; Aubakirova, Karlygash (Acta Biologica Sibirica, 2025)
This article presents the results of a study assessing the state of morphological changes in the male generative organs of Scots pine (Pinus sylvestris L.) in Kazakhstan and Poland. The purpose of this study is to assess the transformation of pine pollen under different environmental conditions. Research and pollen sampling were carried out in 2023 in different environmental conditions and in different geographical areas: Astana (Kazakhstan), Bayanaul State National Natural Park (BSNNP) (Kazakhstan) and Poznan (Poland). For cytological analysis, microsporophylls were selected from the middle part of the microstrobilus, the material was stained with 1% Lugol’s pharmaceutical solution, the preparations were studied on a Nikon eclipse E 200 microscope with a magnification of 10x15x40. The results of the analysis showed that the maximum number of disturbances in pine pollen was detected in samples from Poznan - 63%. In the Bayanaul Natural Park and in Astana, pine has fewer anomalies in pollen - 57% and 55%. The most common types of anomalies found in Scots pine pollen in the study areas are: deformed (26.3%), pollen with impaired shell formation (19%) and degraded (7.4%). Under conditions of technogenic pollution in coniferous trees (Pinus sylvestris L.), a higher level of abnormality of pollen grains was revealed than in relatively clean conditions, and a wide spectrum (sterile, deformed and small pollen grains with disturbances (without air sacs, with one and three air bags).